Biocompatible silk/calcium silicate/sodium alginate composite scaffolds for bone tissue engineering. (1st November 2018) - Zheng, Ao; Cao, Lingyan; Liu, Yang; Wu, Jiannan; Zeng, Deliang; Hu, Longwei; Zhang, Xiangkai; Jiang, Xinquan
Highlights: A calcium silicate (CS)/sodium alginate/silk fibroin scaffold was developed. The porous scaffold shows good biodegradation, cytocompatibility, and bioactivity. Mechanical properties and porosity can be controlled by adjusting the CS content. This composite scaffold shows good potential for bone tissue engineering. Abstract: Scaffolds are crucial for bone tissue engineering since their compositions and properties could significantly affect the seeded cells' behavior. In this study, we developed an interpenetrating network hydrogel by utilizing Ca 2+ from calcium silicate (CS) to simultaneously crosslink silk fibroin (SF) and sodium alginate (SA). Afterwards, the hydrogels were lyophilized to obtain scaffolds and systematically evaluated by physical characterizations, in vitro cytocompatibility and alkaline phosphatase (ALP) assay. We found that CS inside the porous structure of SF/CS/SA scaffolds could remarkably enhance hydrophilicity, degradation, compression resistance, bioactivity and pH of SF/CS/SA scaffolds. Scaffolds with CS concentrations of 25% and 12% (25/CS and 12/CS) could dominantly stimulate proliferation of bone marrow stromal cells (BMSCs). Besides, BMSCs cultured with 25/CS and 12/CS scaffolds showed high ALP activity, respectively. Consequently, this study suggested SF/CS/SA scaffolds possess potential in non-loading bone tissue engineering application.